Methods to evaluate earth slip cohesion to build with light earth. (30th March 2020) - Vinceslas, Théo; Lecompte, Thibaut; Hamard, Erwan; Hellouin de Ménibus, A.; Lenormand, Hélène; Colinart, Thibaut
Highlights: Cohesive behaviors of 6 earth are studied through yield stress measurement. The study is based on samples representative of Brittany and Normandy earth natural variability. Existing or new rheological tests are compared to evaluate their accuracy and validity range. Results allow to control an earth slip yield stress knowing its water content. Abstract: Bio-based materials are subject to a growing interest since the nineties to reduce the environmental impacts of the building sector. Light earth is a low impact insulation material. Light earth building methods are based on the use of earth slip, a mix of clayed earth and water, and aggregates or fibers. The earth slip is characterized on site by mason by different means. This study aims to compare different rheological measurements methods in laboratory conditions, and then to define simple and robust tests adapted to any conditions. The study is based on six soil samples. Geotechnical characterizations show that these soils cover a wide range of natural variabilities. Their cohesive behaviors were investigated by measuring the yield stress with a rheometer, a spread test, a dipping test and a rough wall cone test, both developed for the study, and a Marsh cone test. Accuracy and the validity range of each test are presented alongside the needs for light earth applications.